Aaptamine – a dual acetyl – and butyrylcholinesterase inhibitor as potential anti-Alzheimer's disease agent. (31st December 2022) - Miao, Shuang; He, Qianqian; Li, Chen; Wu, Yan; Liu, Mengshan; Chen, Yongshou; Qi, Shizhou; Gong, Kaikai
Abstract: Context: Alzheimer's disease (AD) is a neurodegenerative disorder that affects millions of people worldwide. Acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) are promising therapeutic targets for AD. Objective: To evaluate the inhibitory effects of aaptamine on two cholinesterases and investigate the in vivo therapeutic effect on AD in a zebrafish model. Materials and methods: Aaptamine was isolated from the sponge Aaptos suberitoides Brøndsted (Suberitidae). Enzyme inhibition, kinetic analysis, surface plasmon resonance (SPR) and molecular docking assays were used to determine its inhibitory effect on AChE and BuChE in vitro . Zebrafish were divided into six groups: control, model, 8 μM donepezil, 5 , 10  and 20 μM aaptamine. After three days of drug treatment, the behaviour assay was performed. Results: The IC50 values of aaptamine towards AChE and BuChE were 16.0 and 4.6 μM. And aaptamine directly inhibited the two cholinesterases in the mixed inhibition type, with Ki values of 6.96 ± 0.04 and 6.35 ± 0.02 μM, with Kd values of 87.6 and 10.7 μM. Besides, aaptamine interacts with the crucial anionic sites of AChE and BuChE. In vivo studies indicated that the dyskinesia recovery rates of 5 , 10  and 20 μM aaptamine group were 34.8, 58.8 and 60.0%, respectively, and that of donepezil was 63.7%. Discussion and conclusions: Aaptamine showed great potential to exert its anti-AD effects by directly inhibiting the activities of AChE and BuChE. Therefore, this study identified a novel medicinal application of aaptamine and provided a new structural scaffold for the development of anti-AD drugs.